Ride Quality Control of a Full Vehicle Suspension System Featuring Magnetorheological Dampers With Multiple Orifice Holes - Oh, Jong-Seok; Choi, Seung-Bok (Frontiers in Materials, 2019)
This study proposes the relationship between the ride comfort of passenger vehicles and two different types of magnetorheological (MR) dampers: with and without orifice holes in the piston. To achieve this, two cylindrical-type MR dampers with identical dimensions such as the radius of piston, pole lengths, and the distance between two poles are proposed. One of the MR dampers adds the orifice holes in the piston bobbin to obtain a relatively low damping force slope in low piston velocity region. In order to enhance the ride quality of passenger vehicle, the damping force slope of rear damper should be more gradual than that of front damper. So, it can be inferred that identical semi-active vehicle systems require normal MR dampers in the front and MR dampers with orifice holes in the rear with proper control strategies. To evaluate the ride performance, a robust sliding mode controller is designed. It is demonstrated through a simulation that the proposed vehicle system produces better ride comfort than vehicle systems equipped with only one type of MR damper.